Pengaruh Pemberian Stimulasi Metode Bercakap-Cakap Terhadap Kreativitas Menggambar Anak Usia Dini - Yulistiana Yulistiana; Dede Ridwan; Muh Hasan Marwiji (Institut Madani Nusantara, 2021)
This study aimed to determine the stimulation of the conversational method in Kartini 3 Kindergarten, Nagrak, Sukabumi Regency before being stimulated by the conversational method, and the creativity of children's drawing and the effect of stimulating conversational method on the drawing creativity of children in Kartini 3 Kindergarten. Nagrak, Sukabumi Regency. The method used in this study was a quasi-experimental method, which aimed to determine the effect of the independent variable on the dependent variable after being stimulated by the conversational method. Quasi-experimental research was conducted because the researchers did not use the randomization technique (samples were randomized) but used groups that were already available (intact groups) at school. The results showed that the final ability of draw creativity of the experimental group who received treatment with the stimulation of the conversational method appeared a significant difference compared with control class. Stimulation of the conversational method has been shown significant effect on increasing children's drawing creativity.